. The clinical value of serum hyaluronic acid, procollagen III, N-terminal propeptide levels sST2 and cfDNA in children with severe pneumonia complicated by myocardial damage: serum hyaluronic acid, procollagen III, N-terminal propeptide levels sST2 and cfDNA in children - Jia, Haoran (Journal of Medical Biochemistry, 2024)
【Abstract】Objective: The paper aimed to explore the clinical value of serum hyaluronic acid, procollagen III, N-terminal propeptide levels sST2 and cfDNA in guiding strategies for children with severe pneumonia complicated by myocardial damage. Methods: 140 children with severe pneumonia admitted to our hospital from May 2022 to April 2024 were clinically recruited as research subjects. According to whether the patients had myocardial damage, they were separated into a group with complicated myocardial damage (n=90) and a group without complicated myocardial damage. group (n=50). Children with myocardial damage were separated into a control group and an observation group. The control group (n=45) was given traditional care, and the observation group (n=45) was based on biomarkers (sST2 and cfDNA) levels guide the development of nursing strategies. Statistics of patients' general information based on clinical files. The patient's serum hyaluronic acid, procollagen III, N-terminal propeptide, sST2 and cfDNA levels were detected through biochemical analysis. Logistic regression was used to unpack the risk element affecting myocardial damage in children with pneumonia. The effectiveness of each biomarker in predicting severe pneumonia complicated by myocardial damage was analyzed based on the ROC curve. The levels of myocardial injury markers NT-proBNP, CK, CK-MB and C-reactive albumen in the control group and observation group were tested by enzyme-linked immunosorbent assay and enzyme activity assay. The clinical treatment effects of the two groups of patients were compared. Results: There was no distinguish in the general record of the two groups (P>0.05). The serum levels of hyaluronic acid, procollagen III, N-terminal propeptide, sST2 and cfDNA in invalids with complicated myocardial damage were higher than the group without myocardial damage (P
Keywords: Serum hyaluronic acid; procollagen III; NT-proBNP; sST2; cfDNA; clinical value